Histology of the Lung Tissue in Dog Faced-water Snake, Cerberus rynchops from Pranburi Estuary, Thailand - เสนารัตน์, ศิลปชัย; บุญยัง, ปิยากร; เพ็งสกุล, ธีรกมล; วังกุลางกูร, ศันสรียา; วงศ์ธรรมวานิช, ณัฐรินทร์; พูลประเสริฐ, พิสิษฐ์; เกษตระฑัต, เจษฏ์ (YRU Journal of Science and Technology, 2017)
In the present study, histological structure of lung tissue in dog faced-water snake, Cerberus rynchops, from Pranbury estuary, Thailand was described using standard histological technique with the staining of H&E and PAS. The results revealed that the lung separated into various parts including bronchus, bronchiole, terminal bronchiole, respiratory bronchiole and alveolar sac, respectively. Alveolar sac was the large area of lung, which composed of numerous alveoli. The respiratory wall of lung tissue of C. rynchops was consisted of mucosa, submucosa, cartilaginous layer and adventitia. The wall of these alveoli was specially structured in thin epithelium and infiltrated by four cell types including 1) type 1 alveolar cell, 2) type 2 alveolar cell, 3) endothelial cell and 4) macrophage. Additionally, numerous capillaries were also observed among the alveoli.